2010
DOI: 10.1097/pgp.0b013e3181c6d965
|View full text |Cite
|
Sign up to set email alerts
|

Pure Primary Squamous Cell Carcinoma of the Ovary: A Report of Two Cases and Review of the Literature

Abstract: Pure primary squamous cell carcinoma (SCCa) of the ovary not associated with pre-existing ovarian lesions including dermoid cysts, Brenner tumors, or endometriosis is extremely rare. The last 2 types of SCCa and pure primary SCCa have been classified by the World Health Organization criteria as surface epithelial-stromal tumors. On account of the rarity of pure primary SCCa of the ovary, the clinical features and effective treatments have not been established. This study describes 2 such cases that we recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…Young et al 10 have identified epidermoid cysts, some in concert with small Walthard rests, but in the absence of any other teratomatous features. Other case reports and small series [11][12][13][14][15][16][17][18][19] have identified de novo squamous cell carcinoma of the ovary, some associated with endometriosis. By all accounts, these entities are exceedingly rare, and questions remain about their histogenesis.…”
Section: Epidemiologymentioning
confidence: 99%
See 4 more Smart Citations
“…Young et al 10 have identified epidermoid cysts, some in concert with small Walthard rests, but in the absence of any other teratomatous features. Other case reports and small series [11][12][13][14][15][16][17][18][19] have identified de novo squamous cell carcinoma of the ovary, some associated with endometriosis. By all accounts, these entities are exceedingly rare, and questions remain about their histogenesis.…”
Section: Epidemiologymentioning
confidence: 99%
“…[11][12][13][14][15][16] In their case series, Pins et al 9 noted that squamous cell carcinoma (arising in association with a dermoid, with endometriosis or de novo endometriosis) usually presents at 52 years; it would seem, therefore, that nonmetastatic squamous cell carcinoma of the ovary is a disease of perimenopausal women, again in contradistinction to a number of other aggressive ovarian neoplasms. A review of reported cases, [6][7][8][9][10][11][12][13][14][15][16][17][18][19] furthermore, suggests that most cases of primary squamous cell carcinoma of the ovary present at advanced stages.…”
Section: Clinical Presentation and Workupmentioning
confidence: 99%
See 3 more Smart Citations